The Influence of Workload and Work Environment on Employee Performance (Study on Kelurahan In Gedebage Subdistrict, Bandung City) - Rahayuningtyas, Puji; Jusdijachlan, R.; Mulyana, Agus (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this study was to find out and analyze: (1) Workload (2) Work Environment; (3) Employee Performance; and (4) The Effect of Workload and Work Environment on the Performance of Kelurahan Employees in Gedebage District, Bandung City, both simultaneously and partially. The research method used in this study is a descriptive survey and an explanatory survey. The unit of analysis in this study was the staff of the Kelurahan in Gedebage District, Bandung City with a sample of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the Workload experienced by the Kelurahan employees in the Gedebage Subdistrict of Bandung City was good, the Work Environment in the Kelurahan in Gedebage District, Bandung City in general could be said to be good, the performance of Kelurahan Employees in Gedebage Subdistrict, Bandung City was now considered good. Workload and Work Environment affect the performance of Kelurahan employees in Gedebage District, Bandung City simultaneously and partially. But partially the dominant workload affects employee performance rather than the work environment. Because the Workload is more dominant in influencing Performance, it becomes the first priority in improving the Performance. Therefore, Kelurahan in Gedebage District, Bandung City is advised to improve the working conditions and atmosphere, so that they are able to work more professionally